A New Technique for Visualization of Latent Fingerprints on Different Surfaces Like Kitchen Appliances and Plastics Using Banana Stem Powder (Musa Sapientum) - S.Kesava priya, Dr. Abirami Arthanari, Dr. Rajeshkumar (Drugs and Cell Therapies in Hematology, 2021)
Introduction: The method of comparing two instances of friction ridge skin impressions from human fingers or toes, or even the palm of the hand or sole of the foot, is fingerprint identification, referred to as dactyloscopy, or hand print identification, to decide if these impressions may have come from the same person. Aim: The aim of the research is to find the new technique for the identification of latent fingerprints using banana stem powder (musa sapientum) on different surfaces like kitchen appliances and plastics. Materials And Methods :The method used in this study was original research.This research should be continued to trials. The sample is taken in powder form. Based on the previous research work articles will be collected and the work is carried out accordingly. Banana stem (musa sapeitum) is collected and dried for 7 days. Fingerprint powder is applied by brushing it on the surface. It mechanically adheres to the oil and moisture components of the latent print. And pictures of those fingerprints are taken for records. Results And Discussion: The result obtained in this study was the banana stem powder shows better results in kitchen surfaces. Fingerprint powder is usually a very fine powder that is either black or white. White powder is used on transparent surfaces for dust impressions, and dark powder is used on light coloured surfaces for dust impressions. Most researchers use black surface talcum-based powders and white surface graphite-based powders. Conclusion: Thus from the above results, the banana stem powder (musa sapientum), we can get visible fingerprints and also we can make fingerprints using the powder.